The Novel Coupling of Operando Methods: Electrochemical Dilatometry with Mass Spectrometry Using the Example of a Li|Graphite Half Cell - Jan Petit; Philipp Heugel; Sebastian Geiger; Franziska Klein; Jens Tübke (Batteries)
The aging of lithium-ion cells critically affects their lifetime, safety, and performance, particularly due to electrode and electrolyte degradation. This study introduced a novel combined-measurement cell-integrating operando dilatometry and operando mass spectrometry to observe real-time physical and chemical changes during electrochemical cycling. Operando dilatometry measures thickness changes in the working electrode, while operando mass spectrometry analyzes gas emissions to provide insights into the underlying degradation processes. The results indicated significant correlations between electrochemical behavior, thickness changes, and gas evolution, revealing both the reversible and irreversible growth of constituents on particles and the electrode surface. The formation of the solid electrolyte interphase due to the degradation of electrolyte components, such as solvents or conductive salts, is identified as a key factor contributing to irreversible changes. The operando gas analysis highlighted the presence of decomposition intermediates and products, which are all linked to electrolyte degradation. Additionally, post-mortem gas chromatography coupled with mass spectrometry identified several compounds, confirming the presence of different decomposition pathways. This integrated and holistic approach deepened the understanding of the aging mechanisms at the electrode level.